Association of putative ammonium exporters Ato with detergent-resistant compartments of plasma membrane during yeast colony development: pH affects Ato1p localisation in patches - Ricicová, Markéta; Kucerová, Helena; Váchová, Libuse; Palková, Zdena (Biochimica et biophysica acta, 2007)
It was proposed that Ato1p, Ato2p and Ato3p have a role in ammonia production by Saccharomyces cerevisiae colonies (Palkova et al., Mol Biol Cell 13: 3901-3914, 2002). In this study, we show that all three Ato proteins localise to the plasma membrane and their appearance correlates with the beginning of ammonia release. The expression of ATO genes is controlled by ammonia. All three Ato-GFP proteins associate with detergent-resistant membranes; two of them, Ato1p-GFP and Ato3p-GFP, localise to patches visible under the fluorescence microscope. In contrast with Ato3p-GFP which forms stable patches, the formation of those of Ato1p-GFP is pH dependent. Ato1p-GFP patches form at pH above 6 and they disappear at pH 5 or lower. Both changes, Ato1p-GFP clustering and patches spreading are reversible. The Ato1p-GFP spreading at low pH is independent on endocytosis. These data suggest that besides the ammonia induction of Ato protein synthesis, pH may rapidly regulate Ato1p function.
Keywords: buněčná membrána; membránové transportní proteiny; Membrane Proteins; kompartmentace buňky; transport proteinů; Recombinant Fusion Proteins; zelené fluorescenční proteiny; Protein Transport; Saccharomyces cerevisiae - proteiny; Green Fluorescent Proteins; Membrane Transport Proteins; Ammonia; Saccharomyces cerevisiae Proteins; detergenty; Hydrogen-Ion Concentration; rekombinantní fúzní proteiny; kvartérní amoniové sloučeniny; Saccharomyces cerevisiae; membránové proteiny; Quaternary Ammonium Compounds; Cell Membrane; Detergents; koncentrace vodíkových iontů; Cell Compartmentation; amoniak